2017
DOI: 10.1128/msphere.00005-17
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Relationships between Fecal Microbiota and Metabolome following Distinct Antibiotic-Induced Disruptions

Abstract: Despite the fundamental importance of antibiotic therapies to human health, their functional impact on the intestinal microbiome and its subsequent ability to recover are poorly understood. Much research in this area has focused on changes in microbiota composition, despite the interdependency and overlapping functions of many members of the microbial community. These relationships make prediction of the functional impact of microbiota-level changes difficult, while analyses based on the metabolome alone provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 75 publications
2
32
0
Order By: Relevance
“…The transient changes that were seen were primarily in bacteria predominantly associated with the rumen microbiota (Prevotellaceae, Rikenellaceae, Christensenellaceae, and Erysipelotrichaceae; Mao et al, 2015 ). Further, the relatively small, short-lived changes found in steers treated with enrofloxacin is in contrast to findings in chickens (Li et al, 2017 ), mice (Choo et al, 2017 ), and humans (Stewardson et al, 2015 ; Pop et al, 2016 ) administered a fluoroquinolone that demonstrate significant changes at the phylum and genus levels which persist for a week or more. Potentially, the large microbial population of the rumen provides a source of microbes to continually repopulate the intestinal environment, leading to minimal changes in the fecal microbiota in ruminants compared to simple-stomached animals.…”
Section: Discussionmentioning
confidence: 67%
“…The transient changes that were seen were primarily in bacteria predominantly associated with the rumen microbiota (Prevotellaceae, Rikenellaceae, Christensenellaceae, and Erysipelotrichaceae; Mao et al, 2015 ). Further, the relatively small, short-lived changes found in steers treated with enrofloxacin is in contrast to findings in chickens (Li et al, 2017 ), mice (Choo et al, 2017 ), and humans (Stewardson et al, 2015 ; Pop et al, 2016 ) administered a fluoroquinolone that demonstrate significant changes at the phylum and genus levels which persist for a week or more. Potentially, the large microbial population of the rumen provides a source of microbes to continually repopulate the intestinal environment, leading to minimal changes in the fecal microbiota in ruminants compared to simple-stomached animals.…”
Section: Discussionmentioning
confidence: 67%
“…While the impact of clindamycin and ciprofloxacin treatment on the mouse gut microbiome has been studied in detail before, usually in context with medical or probiotic interventions, we have found no studies on the effect on the mouse gut microbiome of cefuroxime or dicloxacillin (or any other isoxazoyl penicillin (oxa-, cloxa-, flucloxa-, or nafcillin)). There are studies focusing on the mouse gut microbiome using other cephalosporins or clindamycin and studies focusing on the human gut microbiome using cephalosporins and ciprofloxacin [11][12][13]. Most of these studies have focused on susceptibility to infection, yet to our knowledge there are no studies investigating the effect of dicloxacillin on the gut microbiome nor have any study compared the effect with other antibiotics [11][12][13].…”
Section: Discussionmentioning
confidence: 99%
“…There are studies focusing on the mouse gut microbiome using other cephalosporins or clindamycin and studies focusing on the human gut microbiome using cephalosporins and ciprofloxacin [11][12][13]. Most of these studies have focused on susceptibility to infection, yet to our knowledge there are no studies investigating the effect of dicloxacillin on the gut microbiome nor have any study compared the effect with other antibiotics [11][12][13]. Finally, the majority of studies have focused on susceptibility to infection with specific pathogens such as Clostridium difficile, enterococci spp., salmonella spp., EPE, etc.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it might be premature to ascribe the depletion of the Bacteroidales S24-7 family to changes in oxygen levels. Interestingly, Choo et al (2017) also reported the depletion of the Lachnospiraceae and Ruminococcaceae and the increases in the Enterobacteriaceae and Lactobacillaceae in mice treated with vancomycin and imipenem [ 51 ], suggesting that they may be competitors with each other under non-inflammatory conditions. Further studies of how these commensal bacteria establish their ecological niches in the gut will help to illustrate the mechanisms for the improvement of the IBD-associated dysbiosis.…”
Section: Discussionmentioning
confidence: 99%